Survey of Mental Health Care Providers’ Perspectives on the Everyday Ethics of Medical-Aid-in-Dying for People with a Mental Illness - Montreuil, Marjorie; Séguin, Monique; Gros, Catherine; Racine, Eric (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2020)
Context: In most jurisdictions where medical-aid-in-dying (MAiD) is available, this option is reserved for individuals suffering from incurable physical conditions. Currently, in Canada, people who have a mental illness are legally excluded from accessing MAiD. Methods: We developed a questionnaire for mental health care providers to better understand their perspectives related to ethical issues in relation to MAiD in the context of severe and persistent suffering caused by mental illness. We used a mixed-methods survey approach, using a concurrent embedded model with both closed and open-ended questions. Findings: 477 healthcare providers from the province of Québec (Canada) completed the questionnaire. One third of the sample (34.4%) were nurses, one quarter psychologists (24.3%) and one quarter psycho-educators (24%). Nearly half of the respondents (48.4%) considered that people with a severe mental illness should be granted the right to opt for MAiD as a way to end their suffering. Respondents were more likely to feel comfortable listening to the person and participating in discussions related to MAiD for a mental illness than offering care or the means for the person to access MAiD. Most (86.2%) reported that they had not received adequate/sufficient training, education or preparation in order to address ethical questions surrounding MAiD. Conclusions: The findings highlight how extending MAiD to people with a mental illness would affect daily practices for mental healthcare providers who work directly with people who may request MAiD. The survey results also reinforce the need for adequate training and professional education in this complex area of care.